Workshop Response Time at the Emergency Room Lubuk Pakam Health Center - Ramadhan Ritonga, Rahmad; Kurata’ain, Kurata’ain (JURNAL PENGMAS KESTRA (JPK), 2024)
Higher level of achievement of the community in the local area, this is also a service in the area which is a world-class public and individual service, at the same time prioritized in promotion and prevention efforts. Decree of the Minister of Health Number 129 of 2008 concerning Minimum Service Standards in Emergency Installations, Response Time, also known as "emergency service response time", is the time needed by patients from the time they arrive at the Emergency Installation until they are given first aid in minutes. The maximum response time is five minutes. The results of the study showed that the number of qualified nurses, the availability of medical equipment, and emergency room employees are the main factors affecting response time. An important factor in evaluating the quality of health services is patient satisfaction, which is measured by how patients act after receiving health services. Patient satisfaction also depends on how well the service offers patient expectations. Patient service has a significant impact on patient satisfaction and is an important component in the Puskesmas system that must always be evaluated. The experience and ability of a doctor in handling emergency patients quickly and accurately correlates with patient satisfaction. Patients who receive good health services will indirectly promote and recommend the health facility to their families.